Educators' Awareness of Ergonomics for Digital Education: A Necessity in the New World - Baheti , Radhika S.; Ray , Manish M.; Shyam , Ashok; Sancheti , Parag (Novel Research Aspects in Medicine and Medical Science Vol. 1, 2023)
Covid-19 pandemic resulted in a massive change demanding the world to find newer ways to keep working while staying safe. This is when the teachers were also thrown into a ‘‘new normal’’ of conducting virtual classes and delivering knowledge digitally to support distance learning. In order to address these changes, this study was conducted with an aim to assess school educators’ and understand their level of ergonomic awareness and the importance of its application while conducting teaching sessions virtually. Three key aspects that were mainly highlighted in the study included knowledge about ergonomics and various principles of ergonomics, optimum posturing while taking online lectures and importance of periodic stretch breaks. The study included 97 participants (with a response rate of 71.85%) within the age group of 20-58 years (38.35 ± 10.50) who were sent the self-made questionnaire via online platforms. The questionnaire included several closed-ended questions about the ergonomic principles, sitting postures and workstation set ups. The information so obtained was documented and converted into a computer based spread sheet for data analysis. Based on the outcomes of the study, it was concluded that there is a reduced level of knowledge and awareness of ergonomics in school teachers conducting online lectures. Most teachers who were aware about the usage of a correct sitting equipment (67.4%) were unaware about the necessary adjustments required for its optimal functioning (79.4%). Moreover, 55.6% and 69.1% teachers were unaware about the ideal distance to be maintained between themselves and the computer and mobile screens respectively. The study therefore concluded that the teachers had reduced levels of ergonomic awareness.